Market Dominance and Market Power - Ramamohan Rao, T. V. S. (Cambridge Scholars Publisher, 2020)
This book presents several fundamentally new ideas. It shows that the notion of market dominance depends on the choices of firms. The fundamental idea here is to separate strategies that the firm wishes to pursue and those that it can achieve given the rival reactions. The book also highlights that consumers generally find it difficult to obtain appropriate information about the value of products when many similar products are sold on the market. Firms provide signals in the form of non-price strategies. The identification, by the consumer, of the maximum value of the product may nevertheless.